Prochristianella Dollfus, 1946 (Trypanorhyncha: Eutetrarhynchidae) from elasmobranchs off Borneo and Australia, including new records and the description of four new species - Schaeffner, Bjoern C.; Beveridge, Ian (Zootaxa, 2012)
Prochristianella cairae n. sp. is described from the spiral intestines of two species of bamboo sharks, Chiloscylliumpunctatum Müller & Henle and Chiloscyllium indicum (Gmelin) (Hemiscyllidae) off the coast of Malaysian Borneo. Thespecies is distinguished from congeners by enlarged microtriches covering the whole scolex peduncle, a uniquearrangement of hooks on the basal swelling, a dissimilar number of hooks in each principle row in the metabasal armatureand hook files 1 and 1’ not being distinctly separated. Prochristianella jensenae n. sp. is described from the spiralintestines of three species of whiptail stingrays, Pastinachus solocirostris Last & Manjaji-Matsumoto, Pastinachus atrus(Macleay) and Pastinachus gracilicaudus Last & Manjaji-Matsumoto (Dasyatidae) from coastal waters off Indonesianand Malaysian Borneo and Western Australia, from Himantura uarnak (Gmelin) (Dasyatidae) off Nickol Bay, WesternAustralia and from Rhinoptera neglecta Ogilby (Myliobatidae) off Weipa, Queensland, Australia. This species lacksgland-cells within the tentacular bulbs, one of the most distinctive features of this family. Prochristianella kostadinovaen. sp. is described from the spiral intestines of Himantura uarnak 2 (Dasyatidae) (sensu Naylor et al. 2012) from the Gulfof Carpenteria. It differs from congeners in its metrical data, a metabasal tentacular armature with 10 hooks per principlerow, hooks 1(1’) being uncinate with an elongate base and widely spaced and hooks 4(4’) smaller than neighbouring hooks3(3’) and 5(5’). Prochristianella scholzi n. sp. is described from specimens of the Taeniura lymma species complex(Dasyatidae) (sensu Naylor et al. 2012) from three localities in Malaysian and Indonesian Borneo. This species has arraysof billhooks on the basal swelling, but differs from similar congeners in having very few, tiny gland-cells within thetentacular bulbs and a metabasal tentacular armature with 9–10 hooks per half spiral row and hooks 4(4’) being muchsmaller than the neighbouring hooks 3(3’) and 5(5’). Examinations of new material from northern Australia andIndonesian and Malaysian Borneo provided additional information on Prochristianella aciculata Beveridge & Justine,2010, Prochristianella butlerae Beveridge, 1990 and Prochristianella clarkeae Beveridge, 1990. In total, 17, 7 and 29(respectively) new host records and 14, 9 and 28 (respectively) new locality records are added. These records extend thegeographical range of all three species in the Australasian region and also represents the first record of P. aciculata fromAustralian waters and the first record of P. butlerae from the Indo-Malayan region. Prochristianella clarkeae is the least host specific taxon within Prochristianella, infecting 43 different host species.